Understanding the Core Ideas of Hermeneutics Figures - Prakoso, T; Khasanah, V (KnE Social Sciences, 2018)
This article will talk about core ideas of hermeneutics figures bearing many concepts in the interpretation discipline. Those core ideas are crucial because the scope, postulation, and hypotheses are very comprehensive due to philosophical language making it hard work to understand them. The research methodology applied in this article is qualitative library research. Based on the analysis, it was found that Friederich Schleiermacher was the founding father of hermeneutics. His well-known theory is about intuitive interpretation or intuition-based interpretation. The other problem with this article is about highlighting the other figures’ contribution. Dilthey, Heidegger, Gadamer, Betti, and Hirsch have opposing ideas, albeit somehow identical in some senses, in regard to hermeneutics. Nevertheless, they had an enormously significant impact in hermeneutics. On the other hand, Ricoeur and Habermas impacted hermeneutics differently by introducing new concepts. Ricoeur popularized hermeneutic phenomenology while Habermas claimed the importance of dialogue in understanding a meaning that had three crucial aspects in this world: an objective, social, and subjective world. Keywords: core ideas, hermeneutics figures, intuition-based interpretation